Editorial: which iron preparation for patients with IBD?. Issue 2 (15th June 2017) - Kennedy, N. A.; Goodhand, J. R.; Rampton, D. S.
Abstract : Linked Content This article is linked to Aksan et al papers. To view these articles visithttps://doi.org/10.1111/apt.14126 andhttps://doi.org/10.1111/apt.14043 .